2012
DOI: 10.1007/s10439-012-0631-3
|View full text |Cite
|
Sign up to set email alerts
|

Design and Testing of a Percutaneously Implantable Fetal Pacemaker

Abstract: We are developing a cardiac pacemaker with a small, cylindrical shape that permits percutaneous implantation into a fetus to treat complete heart block and consequent hydrops fetalis, which can otherwise be fatal. The device uses off-the-shelf components including a rechargeable lithium cell and a highly efficient relaxation oscillator encapsulated in epoxy and glass. A corkscrew electrode made from activated iridium can be screwed into the myocardium, followed by release of the pacemaker and a short, flexible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
3
1

Relationship

4
4

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 20 publications
0
27
0
Order By: Relevance
“…7 A single case report provides a pulse-duration curve for a human fetal pacing 4 and is consistent with epicardial pacing parameters in neonates, children and adults. 14 However, as the literature suggests that fetuses exhibit less fibrosis than children and adults, 15 we did not anticipate the observed degree of myocardial inflammation and subsequent capture threshold elevations after electrode placement.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…7 A single case report provides a pulse-duration curve for a human fetal pacing 4 and is consistent with epicardial pacing parameters in neonates, children and adults. 14 However, as the literature suggests that fetuses exhibit less fibrosis than children and adults, 15 we did not anticipate the observed degree of myocardial inflammation and subsequent capture threshold elevations after electrode placement.…”
Section: Discussionmentioning
confidence: 55%
“…As a result, we designed and incorporated a recharging system to allow the pacemaker device to function for the duration of the pregnancy (anticipated 3–5 months). While the technical details of this recharging system are reported separately, 7 it is worth noting that the electronic circuit was redesigned during these experiments such that small fluctuations in the recharging field seen by the micropacemaker would result in relatively large changes in the pacing rate. This modification proved very useful for optimizing the recharging time since changes in fetal and maternal positioning could be quickly recognized (by a decrease in the pacer rate) and the recharging coil re-positioned accordingly.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The threshold strength of the electrical stimulus to pace the heart can be minimized by selecting an appropriately sized electrode, thereby maximizing the very limited battery life. In preliminary experiments, we have observed that strained myocardial tissue had a higher threshold for pacing [13], so it is important to design the electrode so that it penetrates the epicardial and myocardial tissues cleanly. The epicardial connective tissue has a complex structure (Fig.…”
Section: Insertion Of the Epicardial Pacing Electrodementioning
confidence: 99%
“…After the birth, the infant could then be implanted with a standard pacemaker with epicardial leads. We have developed a fetal micropacemaker to meet this prenatal need (Loeb et al ., 2013) and are currently performing pre-clinical studies in fetal sheep (Bar-Cohen et al ., 2015). This paper describes a novel electrophysiological method that provides useful insights into the quality of the electrode-tissue interface during the course of such chronic experiments.…”
Section: Introductionmentioning
confidence: 99%